1997
DOI: 10.1002/pro.5560060210
|View full text |Cite
|
Sign up to set email alerts
|

A desolvation barrier to hydrophobic cluster formation may contribute to the rate‐limiting step in protein folding

Abstract: To gain insight into the free energy changes accompanying protein hydrophobic core formation, we have used computer simulations to study the formation of small clusters of nonpolar solutes in water. A barrier to association is observed at the largest solute separation that does not allow substantial solvent penetration. The barrier reflects an effective increase in the size of the cavity occupied by the expanded but water-excluding cluster relative to both the close-packed cluster and the fully solvated separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
128
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(140 citation statements)
references
References 31 publications
(32 reference statements)
11
128
1
Order By: Relevance
“…In this regard, it should be noted that hydrophobic interactions are in general not pairwise additive. Explicit-water simulations of aqueous solutions of methane molecules showed deviations from pairwise additivity in their interactions; but the deviations are mild [38,62,63]. For instance, for the interaction between a pair of polyalanine helices, the total potential based on an implicit-solvent model that assumes pairwise additivity [40] is similar to the corresponding PMF determined by explicit-water simulation [42].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it should be noted that hydrophobic interactions are in general not pairwise additive. Explicit-water simulations of aqueous solutions of methane molecules showed deviations from pairwise additivity in their interactions; but the deviations are mild [38,62,63]. For instance, for the interaction between a pair of polyalanine helices, the total potential based on an implicit-solvent model that assumes pairwise additivity [40] is similar to the corresponding PMF determined by explicit-water simulation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Effects of similar origin are also at work in association of small hydrophobic solutes into a larger aggregate (21,22) and are quantified by the n-particle potential of mean force (PMF) (23)(24)(25)(26). For n Ͼ 3, however, the dimensionality of the system makes calculations of n-particle PMFs computationally prohibitive.…”
mentioning
confidence: 99%
“…The simulation results make the important point that a standard molecular force field is able to simulate the thermodynamics of hydrophobic free energy when a hydrophobic cluster is formed in water [48]. Rank and Baker [49] found that solvent-separated hydrocarbon clusters precede the desolvated clusters found in the interior of large hydrocarbon clusters. Thus, a hydrocarbon desolvation barrier may be important in the kinetics of protein folding [49].…”
Section: Simulation Of Hydrophobic Clustersmentioning
confidence: 92%
“…Rank and Baker [49] found that solvent-separated hydrocarbon clusters precede the desolvated clusters found in the interior of large hydrocarbon clusters. Thus, a hydrocarbon desolvation barrier may be important in the kinetics of protein folding [49]. In both simulation studies [48,49], the authors find that the molecular surface area (defined by Richards [50]) is more useful than water-accessible surface area in analyzing cluster formation.…”
Section: Simulation Of Hydrophobic Clustersmentioning
confidence: 99%